Growth of CdS crystals by the physical vapor transport method - 程红娟 徐永宽 杨巍 于祥潞 严如岳 赖占平 (Journal of semiconductors, 2009)
Based on the physical vapor transport （PVT） method, the growth of large-size CdS crystals inside a vertical semi-closed tube is studied. Firstly, in order to ensure 1D diffusion-advection transport, multi-thin tubes are used in the growth tube. The XRD spectra of the CdS crystal grown in this configuration indicates that the crystal quality has clearly been improved, where the FWHM is 58.5 arcsec. Secondly, theoretical and experimental growth rates under different total pressures are compared; the results show that the experiential growth rate equation is valid for our semi-tube growth, and it could be used to estimate the growth rate and maximum growth time under different total pressures.